2017
DOI: 10.1186/s40814-017-0195-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes of intestinal microbiota composition and diversity in very low birth weight infants related to strategies of NEC prophylaxis: protocol for an observational multicentre pilot study

Abstract: BackgroundAt the Division of Neonatology, Department of Paediatrics, Medical University Graz, a unique regimen of necrotizing enterocolitis (NEC) prophylaxis in preterm infants showing a < 1500 g birth weight (i.e. very low birth weight, VLBW) is used. The regimen includes oral antibiotic and antifungal therapy and probiotic preparations as well as a standardised feeding regimen. The incidence of NEC in preterm infants treated by this regimen has been shown to be lower, reflecting 0.7% when treatment was initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Table 1 depicts the local regimens used. A detailed study protocol has been published recently [21]. The NEC incidence in Southern Austria was found to be 2.9% (Center G: 2.7%, L: 4.6% and K: 2.2%) during the study period of 2007 to 2016.…”
Section: Study Design Recruitment and Ethicsmentioning
confidence: 99%
“…Table 1 depicts the local regimens used. A detailed study protocol has been published recently [21]. The NEC incidence in Southern Austria was found to be 2.9% (Center G: 2.7%, L: 4.6% and K: 2.2%) during the study period of 2007 to 2016.…”
Section: Study Design Recruitment and Ethicsmentioning
confidence: 99%
“…We conducted a prospective, triple-center cohort pilot study investigating the gut microbiome of preterm infants with a birthweight < 1,500 g in three Austrian neonatal intensive care units (NICUs). These centers (Klagenfurt, K; Leoben, L; Graz, G) used different regimens for NEC prophylaxis which are summarized in Table 1 and have been described in detail previously (Kurath-Koller et al, 2017) (Kurath-Koller et al, 2020). A detailed description of the study design is available in (Kurath-Koller et al, 2017) and first results have already been published elsewhere (Kurath-Koller et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…These centers (Klagenfurt, K; Leoben, L; Graz, G) used different regimens for NEC prophylaxis which are summarized in Table 1 and have been described in detail previously (Kurath-Koller et al, 2017) (Kurath-Koller et al, 2020). A detailed description of the study design is available in (Kurath-Koller et al, 2017) and first results have already been published elsewhere (Kurath-Koller et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Activation of NKT cells is also promoted by Lactococcus , resulting in a cellular immunity, helping to prevent cancer development [ 66 ]. Streptococcus can produce anti-oxidant metabolites that neutralise peroxide and superoxide radicals, preventing DNA damage [ 69 ]. Urbaniak et al also reported a greater abundance of Prevotella in healthy tissues.…”
Section: Tumour Microenvironmentmentioning
confidence: 99%